Role of Intraoral Scanners in the Detection of Dental Caries: A Review - Nikita Sebastian; Ankita Singh; Paras Mull Gehlot; Annapoorna Ballagere Mariswamy (Journal of Clinical and Diagnostic Research, 2022)
Dental caries is an irreversible, microbial disease of the tooth which is characterised by demineralisation and dissolution of the hard tissues. Conventional methods such as visual and tactile examination, radiography, laser or light induced fluorescence methods help in the diagnosis of dental caries, though they lack sensitivity. Being an irreversible process, it is important to detect the caries process in its incipient stages. Very recently, intraoral scanners have also found their way through to the detection and diagnosis of dental caries, particularly, the incipient lesions. Use of advanced technology for the detection of dental caries in its incipient stages has enabled a change in the paradigm to minimally invasive dentistry which focuses more on a preventive approach to caries management. The present review paper attempts to summarise the available literature on the role of intraoral scanners in caries diagnosis by performing a online search on PubMed, Embase, SCOPUS and MEDLINE databases. Only full text studies authored in English and published in peer reviewed journals between 2010 and 2022 were included in the research. Keywords and terms from both review articles and original research papers were taken. A total of 36 papers were reviewed including full texts and abstracts.